2004
DOI: 10.1042/cs20040137
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery stiffening does not explain baroreflex impairment in pre-eclampsia

Abstract: Stiffening of the barosensory vessel wall in hypertension has been suggested to play a role in the associated baroreflex impairment. The carotid distensibility-BRS (baroreflex sensitivity) relationship, however, has not been studied in pre-eclampsia, a condition where hypertension is spontaneously reversible. Twelve normotensive pregnant women and 12 patients with pre-eclampsia matched for maternal age and week of gestation were studied in the third trimester and 3 months postpartum. Carotid artery diastolic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
(37 reference statements)
1
16
0
Order By: Relevance
“…Studies assessing stiffness index in preeclamptic women found similar results [43,47]. Additional records identified through other sources (n = 5)…”
Section: Longitudinal Studiessupporting
confidence: 66%
See 2 more Smart Citations
“…Studies assessing stiffness index in preeclamptic women found similar results [43,47]. Additional records identified through other sources (n = 5)…”
Section: Longitudinal Studiessupporting
confidence: 66%
“…Mersich et al [47] found stiffness index to be significantly elevated in preeclamptic women as compared with normotensive controls during the third trimester and 3 months postpartum.…”
Section: Records Excluded (N = 2964)mentioning
confidence: 97%
See 1 more Smart Citation
“…Reflex responses to atrial stretch are also blunted (51,94,95,103), which may contribute to retention of the expanded blood volume. The depressed baroreflex function observed during normal pregnancy appears to worsen in pregnancy-associated diseases such as preeclampsia (69,129,137,175,195). Interestingly, early gestational measurements of depressed baroreflex sensitivity in conjunction with reduced uterine perfusion have been proposed as a means to predict the ultimate development of this disease (194).…”
mentioning
confidence: 99%
“…Recent progress of the ultrasound equipment enabled us to assess the vascular wall structure and property. Marsich and colleagues measured the vascular wall distensibility of the carotid artery calculated from the blood pressure change and vascular diameter change using an echo-tracking system, and they reported that in patients with pre-eclampsia the carotid artery distensibility was significantly lower than that in normotensive pregnant women [5]. They also reported that in normotensive pregnant women no correlation was found between changes in carotid artery and systemic artery in elastic parameters of the vascular wall [6].…”
Section: Methodsmentioning
confidence: 95%